An Analysis of Social Deixis in the Madness of King George Movie - Zovi Dwi Putra; Dedi Sofyan; Barnabas Sembiring (Yayasan Karinosseff Muda Indonesia, 2020)
This research was aimed at finding out the kinds of social deixis and to explain the social stratification factors in each kind of social deixis in The Madness of King George movie. The type of this research was descriptived qualitative research. Instrument of research that used in this research is the documentation (library research). The matrix table used to collect the data about social deixis in the Madness of King George Movie. According to the matrix table, there are 965 kinds of Relational Social Deixis and 504 kinds of Absolute social deixis used in this movie. The dominant type of Relational Social Deixis is first personal pronoun which refers to the speaker itself. It was used 279 times from total of social deixis used in this movie. In Absolute Social Deixis category, the dominant type was “Sir” which was used 144 times. It was also explained that Relational Social Deixis category is dominant with the frequency of usage around 965 times more than Absolute Social Deixis with the frequency of usage around 504 times from total of social deixis used in this movie. Third, there were three factors of social stratification used in all utterances contained social deixis in this movie. It was found that the dominant social deixis, whether Relational or Absolute Social Deixis, refered to the male characters than the female characters. Because in the 19th century, the man held more power to lead the society and dominant in public relations, especially in Kingdom territory.